1966
DOI: 10.1063/1.1726558
|View full text |Cite
|
Sign up to set email alerts
|

Theory for the Plasticity of Glassy Polymers

Abstract: We present a theory for how a shear stress alone can induce structural changes in a glassy polymer to break up the rigidity of the glass and allow flow. We consider a molecular model in which the shear-stress field is introduced as a bias on the rotational conformation of backbone bonds. It is argued that the fraction of flexed bonds is transiently increased from that in the glass and that this, additionally causing a volume increase, produces a polymer structure resembling the liquid at some temperature above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
150
1
8

Year Published

1991
1991
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 361 publications
(171 citation statements)
references
References 29 publications
5
150
1
8
Order By: Relevance
“…Remark 3: There are many models for the rate and temperature-dependent yield strength of polymers in the literature which consider plastic flow as a thermally-activated process (e.g., Eyring, 1936;Robertson, 1966;Argon, 1973). Most of these models give a reasonably acceptable representation of the variation of the yield strength with temperature and strain rate, but over limited ranges of these variables.…”
Section: Wherementioning
confidence: 99%
“…Remark 3: There are many models for the rate and temperature-dependent yield strength of polymers in the literature which consider plastic flow as a thermally-activated process (e.g., Eyring, 1936;Robertson, 1966;Argon, 1973). Most of these models give a reasonably acceptable representation of the variation of the yield strength with temperature and strain rate, but over limited ranges of these variables.…”
Section: Wherementioning
confidence: 99%
“…2(b). Numerous theories have been developed in the literature [13][14][15][16] in order to model the strain rate and temperature dependence of the yield stress of amorphous polymers over a wide range of strain rate and temperature. However, few models allow reproducing the yield stress of polymers in their glass transition or rubbery regions.…”
Section: Yield Stress Modellingmentioning
confidence: 99%
“…Near a glass transition where a temperature increase produces important structural alterations that increase the fraction of liquid-like material (see Section 11.4.3), different considerations are necessary to change the emphasis from inter-molecular to intra-molecular resistances to deformation. This was achieved by Robertson (1966Robertson ( , 1968) in a theoretical model in which thermal equilibrium concentrations of strain producing "flexed" molecular conformation under the applied shear stress are calculated from Boltzmann statistics through which a structural reference temperature 0 (above Tg) is defined that in turn defines the effective deformation resistance through the free volume model of the glass transition of Williams, Landel and Ferry (1955). Argon and Bessonov (1977a) have compared 'he Robertson model to theirs and have concluded that it should be the model of choice ne-r T,.…”
Section: (-)G = a -B(t/js)mentioning
confidence: 99%